Performance measurement model for monitoring the biathlon centre's environmental impact - Ranta, J. (Lappeenranta-Lahti University of Technology, 2024)
Because of climate change, the warming temperatures pose challenges for winter-dependent sports such as biathlon. The governing body of sports must be aware of the current situation so that future decisions are justified and responsible. Understanding the environmental im pacts of biathlon centres is important for the development of local processes and for reducing the burden on the environment through monitoring.